A randomised, double-blind trial to demonstrate bioequivalence of GP2013 and reference rituximab combined with methotrexate in patients with active rheumatoid arthritis. Issue 9 (21st June 2017) - Smolen, Josef S; Cohen, Stanley B; Tony, Hans-Peter; Scheinberg, Morton; Kivitz, Alan; Balanescu, Andra; Gomez-Reino, Juan; Cen, Liyi; Zhu, Peijuan; Shisha, Tamas
Abstract : Objectives: The aim of this report is to demonstrate pharmacokinetic (PK) and pharmacodynamic (PD) equivalence as well as similar efficacy, safety and immunogenicity between GP2013, a biosimilar rituximab, and innovator rituximab (RTX) in patients with rheumatoid arthritis (RA) with inadequate response or intolerance to tumour necrosis factor inhibitor (TNFi) treatment. Methods: In this multinational, randomised, double-blind, parallel-group study, 312 patients with active disease despite prior TNFi therapy were randomised to receive GP2013 or either the EU (RTX-EU) or the US (RTX-US) reference product, along with methotrexate (MTX) and folic acid. The primary endpoint was the area under the serum concentration–time curve from study drug infusion to infinity (AUC0-inf ). Additional PK and PD parameters, along with efficacy, immunogenicity and safety outcomes were also assessed up to week 24. Results: The 90% CI of the geometric mean ratio of the AUCs were within the bioequivalence limits of 80% to 125% for all three comparisons; GP2013 versus RTX-EU: 1.106 (90% CI 1.010 to 1.210); GP2013 versus RTX-US: 1.012 (90% CI 0.925 to 1.108); and RTX-EU versus RTX-US: 1.093 (90% CI 0.989 to 1.208). Three-way PD equivalence of B cell depletion was also demonstrated. Efficacy, safety and immunogenicity profiles were similar between GP2013 and RTX. Conclusions: Three-way PK/PD equivalence of GP2013, RTX-EU and RTX-US was demonstrated. Efficacy, safety and immunogenicity profiles were similar between GP2013 and RTX. Trial registration number: NCT01274182; Results.